Alterations of the oxidant/antioxidant equilibrium in liver, brain, kidney and heart tissues of offspring born from pregnant rats exposed to Aroclor 1254 alone or in combination with vitamin E - Dogan, A.; Erisir, M. (Ecole Nationale Veterinaire Toulouse, 2011)
The aim of the study was to analyze the oxidant and antioxidant parameters in liver, kidney, brain and heart tissues of offspring from pregnant rats exposed to Aroclor 1254 alone or associated to the vitamin E. A total of 15 pregnant Sprague-Dawley rats were divided into 3 equal groups according to the treatments instituted during the pregnancy period (20 days) - subcutaneous daily injections of Aroclor 1254 (2 mg/kg/day) alone or associated with vitamin E (50 mg/kg/day) or normal saline in controls and were kept with their offspring for 4 weeks. The oxidant / antioxidant balance in the liver, kidney, brain and heart tissues was investigated in 10 slaughtered rat puppies from each group by determining the malondialdehyde (MDA) and glutathione (GSH) contents as well as the superoxide dismutase (SOD), catalase (CAT), and the glutathione peroxidase (GSH-Px), glutathione reductase (GR) and glutathione S- transferase (GST) activities. The Aroclor 1254 exposition during pregnancy has induced significant increases in lipid peroxidation in liver and in brain puppy tissues and various significant alterations of the antioxidant systems according to the considered tissue (increased CAT activities in kidney, heart and brain, decreased SOD activity in brain, increase in the GSH content in liver and decrease in the brain, increased GSH-Px activity in kidney and decrease in heart and marked decrease in the GST activity in liver and increase in brain and kidney). When the vitamin E was simultaneous administered to mothers, the antioxidant systems of the puppies were globally restored to the control values and/or improved and the MDA contents in liver and in heart tissues were efficiently decreased but not in the brain tissues. These results show that the rat pregnant female exposition to Aroclor 1254 induces oxidative damage in the puppies whereas the adjuvant treatment with vitamin E partially alleviates the induced biochemical lesions except in the brain.
Keywords: Polychlorinated biphenyls; Aroclor 1254; Vitamin E; rat; pregnancy; rat puppies; oxidative stress; antioxidants; liver; kidney; brain; heart